Literasi Digital Informasi Kebencanaan selama Erupsi Gunung Semeru pada Perempuan Terdampak di Kabupaten Lumajang Jawa Timur - Ida, Rachmah; Wahyudi, Irfan; Kinasih, Sri Endah; Rozi, Romdhi Fatkhur (Jurnal Aspirasi, 2024)
This research focuses on the importance of disaster information literacy for women's groups. This is crucial as a factor that determines the level of safety of residents in potentially disaster-affected areas, particularly those who had been affected by the eruption of Mount Semeru in 2023 in Lumajang, East Jawa. Through gendered methodology and open ended questions, researchers managed to map the main problems faced by women's groups in accessing important information sources to reduce disaster risk. Conducted between May and June 2023, the research underscored a significant gap in women's literacy concerning digital media, such as social platforms and mobile applications. Even though women are a group that has broad access to social life and can be a liaison of information from outside to all family members. The findings in this study also emphasize the importance of utilizing social capital and integrating women's groups with the government and the main sources of disaster information. By establishing an effective system for distributing disaster knowledge, there is a potential to enhance the disaster information literacy of women's groups and bolster the safety of residents in disaster-prone areas through the implementation of risk communication protocols.Abstrak Penelitian ini berfokus pada pentingnya literasi informasi bencana bagi kelompok perempuan. Hal ini sangat penting karena merupakan faktor penentu tingkat keselamatan penduduk di daerah yang berpotensi terkena dampak bencana, terutama mereka yang terdampak oleh letusan Gunung Semeru pada tahun 2023 di Lumajang, Jawa Timur. Melalui metodologi berbasis gender dan pertanyaan terbuka, para peneliti berhasil memetakan masalah utama yang dihadapi oleh kelompok perempuan dalam mengakses sumber informasi penting untuk mengurangi risiko bencana. Dilaksanakan antara bulan Mei dan Juni 2023, penelitian ini menyoroti kesenjangan yang signifikan dalam literasi perempuan mengenai media digital, seperti platform sosial dan aplikasi seluler. Meskipun perempuan adalah kelompok yang memiliki akses yang luas ke kehidupan sosial dan dapat menjadi perantara informasi dari luar kepada semua anggota keluarga. Temuan dalam penelitian ini juga menekankan pentingnya memanfaatkan modal sosial dan mengintegrasikan kelompok perempuan dengan pemerintah dan sumber utama informasi bencana. Pembentukan aliran distribusi pengetahuan bencana yang baik berpotensi meningkatkan kemampuan literasi informasi bencana kelompok perempuan dan meningkatkan keselamatan penduduk di daerah yang berisiko terdampak bencana melalui protokol komunikasi risiko.